Discovery and druggability evaluation of pyrrolamide-type GyrB/ParE inhibitor against drug-resistant bacterial infection - Xintong Zhao; Jing Feng; Jie Zhang; Zunsheng Han; Yuhua Hu; Hui-Hui Shao; Tianlei Li; Jie Xia; Kangfan Lei; Weiping Wang; Fangfang Lai; Yuan Lin; et al. (Elsevier, 2023)
The bacterial ATP-competitive GyrB/ParE subunits of type II topoisomerase are important anti-bacterial targets to treat super drug-resistant bacterial infections. Herein we discovered novel pyrrolamide-type GyrB/ParE inhibitors based on the structural modifications of the candidate AZD5099 that was withdrawn from the clinical trials due to safety liabilities such as mitochondrial toxicity. The hydroxyisopropyl pyridazine compound 28 had a significant inhibitory effect on Gyrase (GyrB, IC50 = 49 nmol/L) and a modest inhibitory effect on Topo IV (ParE, IC50 = 1.513 μmol/L) of Staphylococcus aureus. It also had significant antibacterial activities on susceptible and resistant Gram-positive bacteria with a minimum inhibitory concentration (MIC) of less than 0.03 μg/mL, which showed a time-dependent bactericidal effect and low frequencies of spontaneous resistance against S. aureus. Compound 28 had better protective effects than the positive control drugs such as DS-2969 (5) and AZD5099 (6) in mouse models of sepsis induced by methicillin-resistant Staphylococcus aureus (MRSA) infection. It also showed better bactericidal activities than clinically used vancomycin in the mouse thigh MRSA infection models. Moreover, compound 28 has much lower mitochondrial toxicity than AZD5099 (6) as well as excellent therapeutic indexes and pharmacokinetic properties. At present, compound 28 has been evaluated as a pre-clinical drug candidate for the treatment of drug-resistant Gram-positive bacterial infection. On the other hand, compound 28 also has good inhibitory activities against stubborn Gram-negative bacteria such as Escherichia coli (MIC = 1 μg/mL), which is comparable with the most potent pyrrolamide-type GyrB/ParE inhibitors reported recently. In addition, the structure-activity relationships of the compounds were also studied.